Deficiency of autophagy leads to significant changes of metabolic profiles in Arabidopsis - Izumi, Masanori (Landes Bioscience, 2013)
Autophagy is an intracellular process leading to vacuolar degradation of cytoplasmic components, which is important for nutrient recycling. Autophagic degradation of chloroplastic proteins via Rubisco-containing bodies is activated in leaves upon low sugar availability in Arabidopsis and our recent study reveals the contribution of autophagy to nighttime energy availability for growth. Whereas metabolic analysis supports that autophagic proteolysis provides a supply of alternative energy sources such as amino acids during sugar deficit, changes in a large number of metabolites due to autophagy deficiency are also observed. Here, we performed statistical characterization of that metabolic data. Principal component analysis clearly separated wild type and autophagy-deficient atg5 mutant samples, pointing to significant effects of autophagy deficiency on metabolite profiles in Arabidopsis leaves. Thirty-six and four metabolites were significantly increased and decreased in atg5 compared with wild type, respectively. These results imply that autophagic proteolysis is linked to plant metabolic processes.